Imaginaries revolving around the Accounting Theory course: The case of the Public Accounting program of the Universidad de la Amazonía - Gómez Cano, Carlos Alberto; Sánchez Castillo, Verenice; García Capdevilla, Diana Ali; García Andrade, Lorena; Barrera Rojas, Yuri Alejandra (Cooperativismo & Desarrollo, 2017)
Introduction: A critical review about accounting education in Colombia, and the importance of accounting theory in the formation of public accountants is presented. This demonstrates the need to articulate ¡ members of the academic communities in order to foster disciplinary development. Methodology: The guiding paradigm was analytical empirical, and the research type was exploratory and descriptive, with survey application. Discussion and results: As a result, the research revealed the wrong interpretation of accounting theory, the shortcomings of teacher action and the apathy of future public accountants on this important issue for the construction of a solid accounting discipline. In addition, emphasis is made on the need for the program’s intervention in order to generate processes of academic transformation. Conclusions: Exhaustive reviews on the course of Accounting Theory, and how it articulates with other academic spaces must be done. This demands the intervention of all members of the university community.